Effectiveness of an Interprofessional Imaging Review Workshop for Radiation Science Students. - Dimopoulos, Maria; Whitton, Joseph; Olsen, Victoria (Radiologic Technology)
Purpose To explore student attitudes, knowledge, experience, and receptiveness to interprofessional education (IPE) in the health sciences and to analyze the effectiveness of an interprofessional imaging review workshop. Methods Participants were recruited from clinical cohorts of the 3 health science programs at Stony Brook University in New York: radiologic technology, radiation therapy, and medical dosimetry. A mixed-methods design was used in which 24 students from these 3 programs were administered the Readiness for Interprofessional Learning Scale (RIPLS) and an imaging assessment before and after a 6-hour interprofessional imaging review workshop. The workshop consisted of didactics, an imaging assessment (ie, image quiz, anatomy labeling), and collaborative case studies. After the interprofessional workshop, participants also completed a survey sharing their experiences and preferences for future training. Results Quantitative findings revealed a substantial and statistically significant improvement in mean quiz scores (46.47% to 82.21%, P < .001, Cohen d = 2.75) and mean anatomy labeling scores (40.00% to 81.70%, P < .001, Cohen d = 2.48) after the workshop. Medical dosimetry students initially exhibited higher competencies compared with radiation therapy and radiologic technology students, but the workshop helped narrow this performance gap. The workshop notably enhanced the Teamwork and Collaboration and the Positive Professional Identity subscales of the RIPLS. In addition, qualitative feedback identified areas for workshop improvement, such as incorporating visual aids and adding case studies specific to certain disciplines. Discussion This project highlights the positive effect of structured IPE, demonstrating its ability to substantially enhance radiation science education and foster collaboration across health care disciplines. Achieving the learning objective of identifying anatomical structures and positively influencing teamwork and professional identity further validates the efficacy of IPE. Based on student feedback and IPE literature, future iterations could integrate a radiologic technology case study, use visual aids for daily professional roles, and consider virtual reality components to enhance learning outcomes and deepen understanding of different health care roles. Conclusion This study demonstrates the substantial positive effect of a 6-hour interprofessional imaging review workshop on enhancing medical imaging learning and fostering positive attitudes toward IPE among radiologic science students.